Nanoindentation of orthodontic archwires: variation of elastic modulus and hardness within a stainless steel wire. (11th January 2008) - Alcock, Joseph; Ireland, Anthony J.; Sandy, Jonathan R.; Barbour, Michele E.
Elastic modulus is one of the critical factors in determining the clinical performance of orthodontic archwires. Hardness is of secondary importance and relates to wire movement and strength. Most techniques which measure mechanical properties require large sections of wire and provide mean values. In this study, atomic force microscopy (AFM) nanoindentation was used to investigate the elastic modulus and hardness of a stainless steel archwire at high spatial resolution. Elastic modulus varied by up to ±17% (p < 0.001) and hardness varied by up to ±22% (p < 0.001), from the mean values. The elastic modulus was slightly higher near the ends than close to the mid-line, but there was apparently random variation superimposed on this trend. Hardness varied apparently randomly throughout the wire. This may partially explain why orthodontic tooth movement is frequently unpredictable.